HUBUNGAN ANTARA KEPRIBADIAN MODEL LIMA FAKTOR DAN PERILAKU BEROLAHRAGA PADA TIM BASKET DI UNIVERSITAS KRISTEN SATYA WACANA - Indhira Vinandha; Aloysius L.S Soesilo (Program Studi S1 Psikologi, 2018)
The purpose of the study is to find out the relationship between the act of doing a certain sport activity and five-factor personality model toward Universitas Kristen Satya Wacana Basketball team. This study uses quantitative method and Purposive Sampling method is used to collect the data. Furthermore, the method of analysis used is Multiple Correlation. To identify the personality variable, the researcher used a translated scale from International Personality Item Pool (IPIP) that was developed by Goldberg (1999). Meanwhile, in order to define the act of doing a sport activity, the scale was made based on the criteria from the theory of Kilpatrick, Herbert, and Bortholomew (2005). This scale was then developed by the researcher and was measured using the Likert scale. This study involved about 62 participants consisted of 35 female participant and 27 male participants ranged from 19 to 22 years old. The result of the study showed a significance level beyond 0.05 (p > 0.05). The result showed that there were no significant relationships toward the dimension of five-factor personality model.